Analisis Manajemen Pemasaran Jasa Lembaga Pendidikan Islam : Pondok Pesantren Amtsilati Darul Falah Bangsri Jepara - Mustaqim, Mustaqim (FITK UIN Walisongo, 2018)
The purpose of this study is to find out how the marketing strategy and marketing services and how its implementation in marketing education services MI, MTS, MA in Pondok Pesantren Darul Falah Bangsri Jepara. This research approach is qualitative with analytic descriptive type. The results of this study found that: The leadership of Darul Falah boarding school (boarding school Amtsilati) perform three strategies. first; analyzing the real needs of santri as potential service users in the form of products / books that are really needed. They find it difficult to understand the yellow book. second: compose a book khulasah (summary) Alfiyah which then called Amtsilati. The number of ba'it (Nazam) is 184, which is the